In vitro Fungicidal Activity of Humic Acid Fraction from Oil Palm Compost - Siddiqui, Yasmeen; Meon, Sariah; Ismail, Mohd Razi; Rahmani, Mawardi; Ali, Asgar (2009)
Fungicidal activity of humic acids isolated from empty fruit bunch of oil palm compost EFB-HA and commercial grade humic acid Co-HA were evaluated on the conidial germination and mycelial growth of Choanephora cucurbitarum. EFB-HA and Co-HA significantly (P ≤ 0.05) inhibited the mycelial growth and conidial germination of C. cucurbitarum in vitro compared to control. The inhibition in mycelial growth increased with increase in humic acid concentrations tested, suggesting the presence of fungicidal activity. The maximum inhibition of conidial germination (71.96% after 24 h) was exerted by EFB-HA at the highest concentration (1000 mg L-1). It was concluded that the efficiency of HA studied in controlling fungal growth was apparently related not only to their concentration and the pathogen examined, but also to HA origin and nature and in particular, HA structural and functional properties, especially COOH group content.